Assessment of climate change vulnerability in Chiti area of Lamjung district, Nepal - Gurung, Sher Bahadur (Geographical Journal of Nepal, 2021)
Climate change issue is the global concern of the present day. The present study attempts to assess the vulnerability of the community due to climate change for which Chiti area of Besisahar Municipality from Lamjung district of Nepal was selected as the study area. The climate change vulnerability was assessed using the Long Term Research Program (LTRP). The long term climate change vulnerability household surveys from 2014 baseline data to 2016, 2017 and 2019 data were analysed in this study. This study adapted IPCC (2001) methodology i.e. also used by C4 EcoSolutions on their baseline climate change vulnerability assessment. This is a bottom-up, integrative approach that considers both physical and social dimensions at a local level. Consequently, vulnerability is best understood as a function of three components: exposure, sensitivity and adaptive capacity. Exposure to climate change vulnerability is calculated with sum of changes in temperature, changes in rainfall patterns, changes in rainfall intensity, drought episodes and flooding events. Sensitivity is calculated based on slope failures, soil fertility, changes in natural environment (i) soil cover; ii) levels of river sedimentation; iii) water salinity; iv) river ecosystems; v) forest size; and vi) the presence of invasive species), economic dependency level, irrigation facilities and livelihood sources. The major finding is that Chiti has been facing climate change since last decade and it is found severely vulnerable due to climate change. There is an urgent need of improvement on climate change adaptive capacity which could result of awareness, information on climate change and adaptation, surplus production and change in agricultural practices. The present study has used awareness score based on conceptual awareness, experiential awareness, and engagement of household to talk about climate change and adaptation. The Long Term Research Approach is appropriate to assess climate change vulnerability in community level. Climate change awareness is one of the major components to reduce vulnerability to climate change in the research area. This is a post adaptation vulnerability analysis of local community which supports climate change vulnerability adaptation policy.